PENGARUH PENILAIAN KINERJA TERHADAP PENINGKATAN KINERJA KARYAWAN PT. ANINDYA MITRA INTERNASIONAL - Anita Verawati (EKBIS (Ekonomi & Bisnis), 2023)
ABSTRACT The objective the study is to determine the performance optimization of employees of PT. Anindya Mitra Internasional after a performance appraisal that affects the amount of performance allowances. This study uses a qualitative descriptive research method, by collecting data, compiling data, presenting data, interpreting data and drawing conclusions to determine the increase in employee performance at PT. Anindya Mitra with a performance appraisal that affects the amount of performance allowances. The variables studied were performance and performance appraisal variables that affect the amount of performance allowances as measured by collecting perceptions through in-depth interviews with employees of PT. Anindya Mitra Internasional and employee performance appraisal variables as measured by achievement in the 2017 – 2021 period and a sample of 10 employees was taken. Keyword: work motivation, performance appraisal, performance allowance